ANALYSIS OF DETERMINANTS OF RED MEAT DEMAND: THE CASE OF URBAN AND PERI-URBAN AREAS OF DENDI AND EJERE DISTRICTS IN WEST SHEWA ZONE, OROMIA NATIONAL REGIONAL STATE, ETHIOPIA - Wegari , Dabesa; Fita, Lemma (International Journal For Research In Business, Management And Accounting, 2021)
The study was aimed at analyzing determinants of red meat demand in the urban and peri-urban areas of Dendi and Ejere districts in West Shewa Zone, Oromia National Regional State. Both qualitative and quantitative data were collected for the study. The data were collected from both primary and secondary sources. The primary data for this study were collected from 155 households by using semi-structured questionnaires, site visit and personal observation. Data analysis was made using descriptive statistics and Tobit regression model. The results of the Tobit regression model indicated that quantity demanded of red meat is significantly affected by household size, religion, income, expenditure, price of the product, fat content of the product, freshness of the product, hygiene, festival and fasting seasons. The red meat demand in the study areas was seasonal and it goes down in major Orthodox Christianity fasting seasons and significantly high on cultural festivals. Therefore, the required recommendations were it is important to support, aware and force hotels and restaurants in providing quality and safety red meat products to consumers. The concerned body should be taken to ensure that the product hygienic is during transportation and handling.